Virtual discussion on anaemia in chronic kidney disease. (2nd November 2020) - Barratt, Jon; Bangura, Bintu; Bhandari, Sunil; Brown, Chris; Hall, Matthew; Mark, Patrick; Mikhail, Ashraf; Williams, Jennifer Ann
Abstract : A group of renal experts attended a round-table meeting to discuss anaemia in chronic kidney disease. Here, Jasmine Callaghan, Journal of Kidney Care (JKC) Editor, details the outcomes